Validitas Konstruk Alat Ukur Spirituality Orientation Inventory (SOI) - Hepi Wahyuningsih (Faculty of Psychology, Universitas Gadjah Mada, 2009)
This research aims to develop Invetory Spirituality Orientation have been made by Elkins et al. (1988). Development of measuring instruments is done with the content validity and construct validity. Content validity test was done by assessing some experts, while construct validity is proved by: (a) evidence of homogeneity, (2) evidence of differences in scores on the two different groups, and (3) factor analysis. Content validity test was conducted by asking five experts of psychology and spirituality to provide a valuation of 90 aitem made with a 5‐point Likert scale (score 1‐5). Test results show the validity of the contents of 90 aitem, 66 aitem valid (the average value of each valid aitem: 4 and up). Tests carried out by the evidence of construct validity of the homogeneity of the internal consistency reliability Cronbach alpha. Cronbach alpha reliability test results show the reliability coefficient of 0.915. Reliability correlation coefficient shows a good homogeneity. Evidence of differences in scores on the two different groups obtained by differentiating groups of subjects who are assumed to have a high spirituality with group of subjects who are assumed to have a common spirituality. Analysis techniques that are used to test differences between groups using the Mann‐Withney. The results show a significant difference between group 1 with group 2 (Mann‐Withney value U = 273.5, Z = ‐3.160, p = 0.002 <0.01). Exploratory factor analysis was done by factor analysis. The number of subjects used for factor analysis of 413 college students of both Muslim men and women. The analysis produced six factors of spirituality, namely: (1) sanctity of life, (2) altruism, (3) idealism, (4) the purpose and meaning in life, (5) transcendent / beliefs, and (6) an awareness of the suffering of the sanctity of life.